2004
DOI: 10.1038/sj.onc.1207476
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumor-associated fatty acid synthase activity antagonizes estradiol- and tamoxifen-induced agonist transactivation of estrogen receptor (ER) in human endometrial adenocarcinoma cells

Abstract: Overexpression of the lipogenic enzyme fatty acid synthase (FAS) is a common molecular feature in subsets of sex-steroid-related tumors including endometrium and breast carcinomas that are associated with poor prognosis. Pharmacological inhibition of tumor-associated FAS hyperactivity is under investigation as a chemotherapeutic target. We examined the effects of the mycotoxin cerulenin (a covalent FAS inactivator), and the novel small compound C75 (a slow-binding FAS inhibitor) on estradiol (E 2 )-and tamoxif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 79 publications
(86 reference statements)
2
20
0
5
Order By: Relevance
“…Tamoxifen and raloxifene were antiestrogens in MCF-7 cells but acted as ER agonists in Ishikawa cells, and exhibited partial estrogenic activities. This conclusion on tamoxifen is consistent with many other studies (Menendez et al, 2004;Shah et al, 2005), but the results with raloxifene differ from some studies and many of these former studies are inconsistent with each other. Raloxifene, a compound for osteoporosis treatment, is being tested for breast cancer therapy.…”
Section: Tissue-specific Effects Of Tamoxifen and Raloxifenesupporting
confidence: 85%
“…Tamoxifen and raloxifene were antiestrogens in MCF-7 cells but acted as ER agonists in Ishikawa cells, and exhibited partial estrogenic activities. This conclusion on tamoxifen is consistent with many other studies (Menendez et al, 2004;Shah et al, 2005), but the results with raloxifene differ from some studies and many of these former studies are inconsistent with each other. Raloxifene, a compound for osteoporosis treatment, is being tested for breast cancer therapy.…”
Section: Tissue-specific Effects Of Tamoxifen and Raloxifenesupporting
confidence: 85%
“…Overexpression of FAS is a common molecular feature in subsets of sex-steroid-related tumors [17,36] including endometrium and breast carcinomas, ovarian and prostate cancers. Pharmacological inhibition of tumour-associated FAS hyperactivity is under investigation as a chemotherapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that protection from cell death and the activation of growth factor signaling are just a few of the newly recognized roles of the lipogenic phenotype in cancer cells. [42][43][44][45][46] Moreover, shifting lipid acquisition from lipid uptake toward de novo lipogenesis enables cancer cells to dramatically alter their membrane properties and protects tumor cells from both endogenous and exogenous insults. 47 As lipogenicity increases, the degree of lipid saturation also decreases, and monounsaturated lipids are less susceptible to lipid peroxidation; together, these observations indicate that the lipogenic switch may protect cancer from free radicals.…”
Section: Mitochondrial H + -Atp Synthase-mediated Energy Adaption: a mentioning
confidence: 99%